(3bUjOI dGHf GdJYGhjPjs - (3GHf GdJYGhjPj, eMeO Hf YHjO Gddg Hf YHO Gddg, J(B583(3g`s
(3ChdgG (B:s
(3Ef cGf Ojfc aj GdUHGHI Ojfj (B*** (3aba GdeWj HQedJj jHQjf , hGdKe KQG dh TGQaJ Hj gVHI (B*** (3CjOj GdeWi dKeJg HLahfjs
(3BNQgG (B:s
(3hef GdefjI Cf Jchf eWGdHj (B*** (3LPhG HNjd Ch (B() (3NDf , djJ GdVjf Ydi GdeMH HhUdg (B*** (3dbf GdSeGMI ef UdGM GdOjfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 6 / 260s
(3eYLe GdeDdajf(B: 3 / 478s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdCOHs